Structure-activity relationship of atorvastatin derivatives for metabolic activation by hydrolases. (3rd March 2020) - Mizoi, Kenta; Takahashi, Masato; Sakai, Sachiko; Ogihara, Takuo; Haba, Masami; Hosokawa, Masakiyo
Abstract: 1. We investigated the structure-activity relationship of 31 kinds of synthesized atorvastatin esters, thioesters, amides and lactone, selected as prodrug models, for metabolic activation by microsomes and hydrolases. 2. The susceptibility to human carboxylesterase 1 (hCES1) was influenced not only by the size of the acyl group and alkoxy group but also by the degree of steric crowding around the alkoxy group. 3. The susceptibility to human carboxylesterase 2 (hCES2) increased with a decrease in electron density around the alkoxy group of the substrate. 4. Lactone was specifically hydrolyzed by paraoxonase 3 (PON3). 5. These findings should be useful in prodrug design for controlling metabolic activation.